Relationship Between Family Support and Foot Care in Diabetes Mellitus Type 2 Patients During Covid-19 Pandemic - Suardi, Suardi; Patmawati, Patmawati; Wirda, Wirda; Ernawati, Ernawati; Dewiyanti, Dewiyanti (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Diabetes Mellitus (DM) is one of the dangerous factors to expand the seriousness of the COVID-19 disease. Older diabetes patients (>60 years), uncontrolled glucose levels, and the presence of diabetic complications were associated with worse COVID-19 suspicion. Aim: The purpose of the study was to determine the relationship between family support and foot care in Type 2 Diabetes Mellitus Patients during the Covid-19 Pandemic in Takalar Regency. Method: The method used is an analytical survey research with a Cross Sectional approach. The sampling technique is Accedential Sampling. The research location is in the Work Area of ??the Bulukunyi Health Center, Takalar Regency with a total sample of 49. The data analysis used the Chis-quare test. Results: The results showed that the value of 0.001 (0.05) this indicates that Ha is accepted and H0 is rejected. Conclusion: There is a relationship between family support and foot care in type 2 diabetes mellitus patients during the Covid-19 pandemic in Takalar Regency. For clinical practitioners, it is necessary to improve foot care in DM patients to prevent further complications through family support, and further research needs to be carried out by looking at HbA1C